2022
DOI: 10.3390/curroncol29040182
|View full text |Cite
|
Sign up to set email alerts
|

Endobiliary Radiofrequency Ablation Combined with Gemcitabine and Cisplatin in Patients with Unresectable Extrahepatic Cholangiocarcinoma

Abstract: Background: Endobiliary radiofrequency ablation (RFA) is a promising treatment modality for patients with extrahepatic cholangiocarcinoma (eCCA). However, no study has investigated the combined use of endobiliary RFA and gemcitabine plus cisplatin (GC) chemotherapy. This study aimed to examine the feasibility and efficacy of endobiliary RFA with GC therapy for patients with unresectable eCCA. Methods: The study outcomes included overall survival (OS), progression-free survival (PFS), time to recurrent biliary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 32 publications
2
25
1
Order By: Relevance
“…RFA works by promoting coagulation necrosis on the targeted area and, consequently, local control of tumor growth [8]. Given the mechanisms of intraductal RFA, research has been undertaken to determine whether RFA could not only improve survival, but also prolongs stent patency rates [9][10][11][12][13]. Despite an increased adoption of intraductal RFA in advanced endoscopy practice, typically limited to high-volume or tertiary centers, there is a paucity of data and guidelines to suggest its use.…”
Section: Introductionmentioning
confidence: 99%
“…RFA works by promoting coagulation necrosis on the targeted area and, consequently, local control of tumor growth [8]. Given the mechanisms of intraductal RFA, research has been undertaken to determine whether RFA could not only improve survival, but also prolongs stent patency rates [9][10][11][12][13]. Despite an increased adoption of intraductal RFA in advanced endoscopy practice, typically limited to high-volume or tertiary centers, there is a paucity of data and guidelines to suggest its use.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the supporting data for biliary RFA therapy have been driven by retrospective studies that showed the potential efficiency and safety of RFA when added to standard stenting [ 14 , 15 ]. To date, RFA has gained momentum, and there are several randomized and prospective trials showing that endobiliary RFA prior to stent placement or at the time of stent occlusion might be efficient and safe in prolonging stent patency or even life expectancy [ 16 , 17 , 18 , 19 ]. Moreover, a relatively recent meta-analysis showed that when added to stent placement RFA increases both survival and stent patency compared to stent placement alone [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that endobiliary RFA is safe and effective for the treatment of MBS 8–28 . A prospective single‐center randomized controlled trial (RCT) involving 68 patients with unresectable extrahepatic cholangiocarcinoma demonstrated that endobiliary RFA combined with plastic stent implantation significantly prolonged overall survival (OS) (13.2 ± 0.6 months vs 8.3 ± 0.5 months, P < 0.001) and the median stent patency time (6.8 months vs 3.4 months, P = 0.02) compared with stenting alone.…”
Section: Indications For Endobiliary Rfamentioning
confidence: 99%